(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
Abstract (100 words) In the evolving realm of warfare, Unmanned Aerial Vehicles demand nuanced consideration for their dual nature. As instruments poised to redefine conflict, drones embody both promise and peril. They serve as valuable tools for police, legal forces, and disaster relief, excelling in surveillance and reconnaissance. However, the demerits of this technological marvel are being made manifest as states and actors employ them for remote strikes in inaccessible locations and against civilians. The expanding role of drones necessitates increased surveillance and rigorous oversight. Striking a balance between their positive potential—and inherent risks—is imperative for navigating the complex landscape of drones.